The Dominant Position of Regional Facilities for the Processing of Municipal Waste - Bujny, Jędrzej; Mądry, Tymoteusz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
This paper addresses the issue of the functioning of regional facilities for the processing of municipal waste in the light of the provisions of the Competition and Consumer Protection Act of 16 February 2007. The authors seek answers to the question of whether in certain specific situations it is possible to conclude that a given facility holds a dominant position on the market in which it operates. Two situations will be subjected to close analysis, namely those in which only one or two facilities with RMWPF status operate in a given region of municipal waste management.